Menyingkap Social Nature Industri Musik Digital dalam Negeri - AWANG DHARMAWAN (Komunikator, 2012)
The object of this paper is the social condition of domestic digital music. The background of this paper is based on the global data that thirty billion songs are downloaded illegally in the period of 2004-2009, with a loss of $17-40 billion. Illegal music downloading is also occurred in Indonesia. Based on the survey of non-governmental organization, Heal Our Music, it was found that there are 7.920.944 illegal downloads of digital music in Indonesia each day. That number means every second there are 92 illegal downloads. Thus, the author mapped three points of the discussion which are the reality of domestic piracy, supporting the copyright of music creative industry, and literacy for music lovers. The conclusion of this paper is that the copyright laws are still inadequate. The government have to provide technical systems to download music legally and cheaply for music lovers. Keywords: Digital Music, Illegal Downloading, Piracy and Literacy